2006
DOI: 10.1086/498635
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Properties of O‐Type Stars

Abstract: We present a comprehensive analysis of high-resolution, far-ultraviolet HST STIS, FUSE, and optical spectra of 18 O stars in the Small Magellanic Cloud. Our analysis is based on the OSTAR2002 grid of NLTE metal-line-blanketed model atmospheres calculated with our code TLUSTY. We systematically explore and present the sensitivity of various UV and optical lines to different stellar parameters. We have obtained consistent fits of the UV and the optical spectrum to derive the effective temperature, surface gravit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
184
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(211 citation statements)
references
References 48 publications
(186 reference statements)
24
184
3
Order By: Relevance
“…The bright end of its stellar population (V ≤ 19.5 mag) has been investigated extensively in the past 20 years. Spectral investigations of the brightest members identified several stars of spectral type O6.5 or earlier (Massey et al 1989;Heap et al 2006;Mokiem et al 2006;Evans et al 2006). Massey et al (1989) found the mass function (MF) of the brightest stars in NGC346-down to 5 M -to have a slope that is consistent with what has been found for massive stars near the Sun and in the Large Magellanic Cloud (LMC).…”
Section: Ngc346supporting
confidence: 60%
See 1 more Smart Citation
“…The bright end of its stellar population (V ≤ 19.5 mag) has been investigated extensively in the past 20 years. Spectral investigations of the brightest members identified several stars of spectral type O6.5 or earlier (Massey et al 1989;Heap et al 2006;Mokiem et al 2006;Evans et al 2006). Massey et al (1989) found the mass function (MF) of the brightest stars in NGC346-down to 5 M -to have a slope that is consistent with what has been found for massive stars near the Sun and in the Large Magellanic Cloud (LMC).…”
Section: Ngc346supporting
confidence: 60%
“…The majority of these stars belong to NGC346, and have an age of ∼3 Myr (Bouret et al 2003;Sabbi et al 2007). Spectral analysis of NGC346 members revealed the presence of stars as young as ∼1 Myr, (Massey et al 2005), but stars aged ∼5 Myr are also present (Heap et al 2006;Mokiem et al 2006). …”
Section: Ngc346 Color-magnitude Diagrammentioning
confidence: 98%
“…The first analysis of surface CNO abundances of O stars and B supergiants tends to confirm the theoretical predictions qualitatively: more evolved stars have a higher N content as a result of CNO processing and mixing (Hillier et al 2003;Heap et al 2006;Crowther et al 2006); however, the role of rotation in explaining the chemical patterns of B stars in the Magellanic Clouds has been questioned by the results of the first ESO/VLT Large Programme dedicated to massive stars (Evans et al 2005(Evans et al , 2006. Hunter et al (2008) showed that 60% of their sample of B main-sequence stars in the Large Magellanic Cloud displayed the nitrogen surface abundances expected by evolutionary models including rotational mixing, but the remaining 40% escaped such an agreement.…”
Section: Chemical Evolution and Rotationmentioning
confidence: 64%
“…During the last years, the quantitative analyses of spectra in the far-UV/UV and optical domains (e.g., Herrero et al 2002;Bianchi & Garcia 2002;Crowther et al 2002;Bouret et al 2003;Repolust et al 2004;Massey et al 2004;Heap et al 2006) have unambiguously shown that the inclusion of line-blocking and blanketing and wind effects (if present) significantly modifies the temperature scale of O-stars (for a recent calibration at solar metallicity, see Markova et al 2004;Martins et al 2005). Regarding B-SGs, particularly of later subtype, this issue has not been addressed so far, mostly due to lacking T eff estimates.…”
Section: Introductionmentioning
confidence: 99%